Die mobile Arbeitsmaschine als komplexes System - Kautzmann, Timo (Karlsruher Schriftenreihe Fahrzeugsystemtechnik / Institut für Fahrzeugsystemtechnik, 2013)
This work discusses the question, how far mobile machines have evolved to complex systems today. Some resulting problems of the conventional strictly decentralized control are revealed. An alternative is the observer/controller architecture, which is transfered to a concrete mobile machine in the simulation.